Human-Centered Ergonomic Design in Industry 5.0: Enhancing Productivity and Worker Wellbeing - Idzani Muttaqin (Balai Besar Standardisasi dan Pelayanan Jasa Pencegahan Pencemaran Industri, 2025)
Industry 5.0 represents a paradigm shift from technology-driven automation to a human-centered approach, emphasizing the integration of advanced technologies with human creativity and well-being at its core. This article employs a qualitative literature review to explore the role of ergonomic design as a foundational pillar within Industry 5.0, focusing on its impact on productivity and worker well-being. The review synthesizes findings from recent studies and bibliometric analyses, highlighting how ergonomic interventions—spanning physical, cognitive, and social domains—optimize work environments by aligning them with human capabilities and limitations. Differentiating from existing literature, this research emphasizes the importance of a holistic ergonomic approach in designing work environments that not only enhance safety and comfort but also foster collaboration between humans and intelligent machines. In Industry 5.0, ergonomic design reduces physical strain and cognitive overload, while simultaneously promoting innovation and job satisfaction. The integration of real-time monitoring technologies and adaptive workstations allows for dynamic adjustments, ensuring sustained worker health and organizational efficiency. However, despite these advancements, challenges remain in the widespread adoption of ergonomic principles, particularly in harmonizing technological innovation with the holistic needs of workers. The findings underscore the necessity of a comprehensive, multidisciplinary approach—bridging policy, technology, and human factors—to fully realize the potential of human-centered ergonomic design in Industry 5.0. This study offers actionable insights for researchers and practitioners aiming to create productive, sustainable, and worker-friendly industrial ecosystems, with an added focus on how ergonomic design in Industry 5.0 fosters more adaptive and dynamic human-technology interactions compared to previous approaches.